Usklajenost dela v ambulanti za spinalno ortotiko s smernicami Združenja za zdravljenje bolnikov s skoliozo (SOSORT) - Pertot, Anja (Rehabilitacija (Ljubljana), 2011)
Background: Scoliosis is a complex structural deformity of the spine, in which there is an abnormal curvature of the vertebral column on all three spatial axes. The condition manifests itself with a lateral curvature on the frontal plane, inversion on sagittal plane and vertebral rotation on axial plane. In smaller curvatures the therapy consists of physiotherapeutic approach and braces. In 2006, the Guideline Committee of the International Society on Scoliosis Orthopaedic and Rehabilitation Treatment (SOSORT) prepared indications for conservative management of scoliosis. The aim of the study was to compare the work in our out-patient clinic at the University Rehabilitation Institute in Ljubljana to those guidelines over a five year period. Methods: Data were collected from patient records of all children treated with brace in the years 2005-2009. We collected basic demographic dataand data on diagnosis, curve magnitude, Risser grade, type of brace, compliance, physiotherapy, number of radiographic controls and therapy outcome. Results: In the studied period, 105 children were treated, 74 girls and 31 boys, with an average age at the first check-up of 12.1 years. The most frequent diagnosis was adolescent idiopathic scoliosis (61%). The mean curve magnitude was 29.3°. Among the 53 cases of idiopathic scoliosis with complete data, 44 were treated according to the SOSORT guidelines. Conclusions: In the majority of the cases, the work in our out-patient clinic was done according to the international guidelines. The existing team of experts has to be upgraded with a specially educated physiotherapist.
Keywords: hrbtenica; opornice; skolioza; smernice; spinalne ortoze; therapy; zdravljenje